PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN GOOGLE SITE TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN INFORMATIKA - Gracelin Mbuik; Maria M. B. Sogen; Jhon Enstein (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the effect of integrating Google Site as an instructional medium on students’ learning interest in the Informatics subject at SMP Kristen Citra Bangsa Kupang. Using a quantitative experimental design with pre-test and post-test measures in control and experimental groups, data were collected through validated questionnaires and structured classroom observations. The results reveal a statistically significant enhancement in students’ learning interest following the implementation of Google Site, reflected in the increased post-test mean score (86.5) compared to the pre-test (72.3). These findings demonstrate that Google Site serves as an effective digital platform that fosters active participation, motivation, and engagement, ultimately creating a more interactive and student-centered learning environment.